Uncovering Wasathiyah Values On Sharia Banking - Amiruddin, Muhammad Majdy; Sapa, Nasrullah bin; Syatar, Abdul (Universitas Islam Negeri Alauddin Makassar, 2020)
Islamic banking in Indonesia has a unique approach. Not only restricted by texts which are the source of rules, he also strongly considers the reality of society in Indonesia. Text and context also struggle to achieve benefit. Something that can only be achieved by the wasathiyah approach. This study aims to reveal the wasathiyah values contained in Islamic banking activities in Indonesia. The method adopted is a qualitative design. As a grand theory, this research uses wasathiyah theory by Yusuf Al Qardhawi. An interesting finding states that wasaty has covered the right understanding related to the usury distinction between interest and profit and wages. Another interesting finding shows that uqud al murakkabah that has been forbidden by the traditionalists in total, is also given an appropriate portion so that halal-haram can be classified